[Chucho and his friends] - Esmerelda Landin::::::photographer::: (2005)
Description supplied by photographer: 'Aquí está mi primo Chucho en compañía de sus amigos. Ellos son una agrupación de muy buenos amigos que se autodenominan '1015'.' Translation of description: 'This is my cousin, Chucho who is hanging out with his friends. They are a group of really close friends who call themselves '1015'.'